Assessing the Wastewater Pollutants Retaining for a Soil Aquifer Treatment using Batch Column Experiments - V. R. Raji; S. Packialakshmi (Civil Engineering Journal, 2022)
In this study, the Secondary Treated Waste-Water (STWW) to infiltrate through the soil matrix, hence eliminating the contaminants in the effluent. For this study, three types of soil, such as loamy sand, fine sand, and clayey soil, were subjected to two cycles of wetting and drying to assess the type of soil that removes the maximum contaminants under which cycle. At diverse locations, soil samples were collected and examined to determine the soil types. Likewise, STWW was collected from Chennai Metropolitan Water Supply and Sewerage Board (CMWSSB) and Perungudi Sewage Treatment Plant (PSTP) to illustrate the quality of water before Soil Aquifer Treatment (SAT). About 1.5 m in height and 8 mm in diameter of fabricated acrylic material columns are used for the soil aquifer treatment efficiency studies. Water quality parameters, namely pH, TDS, and turbidity, were monitored throughout the study. All the organic compounds present in water were reduced to a higher level only in the fine sand in the one-day wetting/drying cycle. pH was reduced from 8.55 to 7.5, TDS was reduced from 1580 mg/l to 850 mg/l, and Turbidity was reduced from 7.24 to 4.04 NTU. This proposed method is to minimize the amount of water pollution from the environment. It is an effective way to manage aquifer recharge (MAR). SAT is the easiest method, aquifer and/or soil-based treatment systems improve the effluent quality of wastewater by removing the trace elements in the aquifer during the recharge of groundwater. It is likewise attractive for technologically advanced as well as emerging countries, and it is supple enough to allow adaptation to home-grown requirements by uniting it with predictable natural or bringing about water and technologies of wastewater treatment. Doi: 10.28991/CEJ-2022-08-07-011 Full Text: PDF